GRAMMATICAL FEATURES OF FUNCTION WORDS IN KARAKALPAK AND ENGLISH LANGUAGES: GRAMMATICAL FEATURES OF FUNCTION WORDS IN KARAKALPAK AND ENGLISH LANGUAGES - Jawgasharova, Amina (Журнал иностранных языков и лингвистики, 2025)
In English grammar books, function words are words that have little lexical or ambiguous meaning and express grammatical relationships which is totally matched with the definitions in Karakalpak language. Grammar is traditionally subdivided into two inter-related studies: Morphology and Syntax. Morphology is the study of how words are formed out of smaller units called morphemes while syntax is concerned with how words are strung together to form larger units of expressions such as (partial) Phrases, Clauses, and (full) Simple Sentences